Grassroots International NGOs: Using Comparative Interpretive Policy Analysis to Understand Meanings in Private Development Aid. Issue 1 (2nd January 2020) - Appe, Susan; Telch, Fabian
Abstract: This research comparatively examines grassroots international NGOs (GINGOs), a growing subset of international nongovernmental organizations (INGOs) working in private development aid. GINGOs are small-scale, on-going development initiatives through voluntary third sector organizations. How do GINGOs' founders and volunteers understand their role in private development aid? The article uses an interpretive framework to examine three in-depth comparative case studies of GINGOs based in the US and working in South Sudan, Nepal and Haiti. Its contribution is that it provides rich data to build further theory about the experiences, or multiple realities, in private development aid. It is found that GINGOs' founders and volunteers attach new meanings to private development aid to distinguish themselves from larger professionalized INGOs and emphasize personal connections.